O sen-tido e o sin-toma no café com Freud - Silva, Iná Maria Nascimento Gomes (2008)
The project Coffee with Freud (CcF) is a proposal supported by an approach of lived experiences. It indicates a space of investigation linked to a theoretical support. It is a happening which can be defined as a place of pulsation. It joins and mobilizes people, a concrete experience which seems to touch the saying borders. It means a language bothering in which a rupture movement threatening other significant. It also provokes effects of mis-sense . Each CcF edition questions a conceptual psychoanalytical framework, involving a discursive and linguistic approach. It considers subjects as language effects, attributed to laws and cultural propositions. CcF is a place of pulsation which emphasizes subject notion as supposed to be not measurable. It is not conditioned to itself. It deals with meanings as a language pulsation passage, as a possibility of feelings expression in the impossibility of feelings saying. One of the theoretical presuppositions of this work deals with the deciding process of CcF themes. Its editions are thematic and there are two guests for exposing the chosen theme. Such choice will constitute an animation trace. This choice supposes to give life, soul and movement to the project idea. Thus, it could be considered as being a story which will be told the so-called mis-sense : a narrative of a misunderstanding condition of human being human contradiction. Another presupposition for such work refers to what Lacan means as being a false step, the needed step for interfering guest participation. In CcF, invited guests, when confirm their participation, they inscribe themselves in a dimension of sin , the beginning of a symptom, according to Lacan. The sin of primordial absence, once there is an enunciatively aesthetics about how to say in the CcF proposal. It provokes a sensation of an interrupted searching which, in fact, is never interrupted. CcF editions are concerned to Lacanian symptom expression. It is a moment in which guests and audience work discursively in their pulsation singularity, associating language, pulsation body and symbol (sin and set; sin and tone). It means an expression of a time which identifies itself to a movement of language subversion. It is an aesthetics dimension. CcF rescues lost words as sense effects.